The intracellular bacterium Rickettsia rickettsii exerts an inhibitory effect on the apoptosis of tick cells - Martins, Larissa Almeida; Palmisano, Giuseppe; Cortez, Mauro; Kawahara, Rebeca; Freitas Balanco, Jose Mario de; Fujita, Andre; Alonso, Beatriz Iglesias; Barros-Battesti, Darci Moraes [UNESP]; Braz, Gloria Regina Cardoso; Tirloni, Lucas; Esteves, Eliane; Daffre, Sirlei; et al. (Bmc, 2020)
Background Rickettsia rickettsii is a tick-borne obligate intracellular bacterium that causes Rocky Mountain spotted fever, a life-threatening illness. To obtain an insight into the vector-pathogen interactions, we assessed the effects of infection with R. rickettsii on the proteome cells of the tick embryonic cell line BME26. Methods The proteome of BME26 cells was determined by label-free high-performance liquid chromatography coupled with tandem mass spectrometry analysis. Also evaluated were the effects of infection on the activity of caspase-3, assessed by the hydrolysis of a synthetic fluorogenic substrate in enzymatic assays, and on the exposition of phosphatidyserine, evaluated by live-cell fluorescence microscopy after labeling with annexin-V. Finally, the effects of activation or inhibition of caspase-3 activity on the growth of R. rickettsii in BME26 cells was determined. Results Tick proteins of different functional classes were modulated in a time-dependent manner by R. rickettsii infection. Regarding proteins involved in apoptosis, certain negative regulators were downregulated at the initial phase of the infection (6 h) but upregulated in the middle of the exponential phase of the bacterial growth (48 h). Microorganisms are known to be able to inhibit apoptosis of the host cell to ensure their survival and proliferation. We therefore evaluated the effects of infection on classic features of apoptotic cells and observed DNA fragmentation exclusively in noninfected cells. Moreover, both caspase-3 activity and phosphatidylserine exposition were lower in infected than in noninfected cells. Importantly, while the activation of caspase-3 exerted a detrimental effect on rickettsial proliferation, its inhibition increased bacterial growth. Conclusions Taken together, these results show that R. rickettsii modulates the proteome and exerts an inhibitory effect on apoptosis in tick cellsthat seems to be important to ensure cell colonization.
Keywords: Apoptosis; Proteome; Rickettsiae; Tick